Research on the high precision hydraulic column stress monitoring method - Jianzhuo Zhang; Chuanxu Wan; Jie Wang; Ce Chen; Tao Wang; Kai Xu (Scientific Reports)
Abstract The hydraulic column is a core component in the coal mine support system, however, the real-time monitoring of the hydraulic column during the service process of the hydraulic support faces challenges. To address these issues, a high-precision stress mapping method of hydraulic column is proposed. The hydraulic column loss function was constructed to guide the data-driven model training, and the cylinder stress mechanism model was established by using the elastic–plastic theory of thick-walled cylinder. The weight coefficients of the data-driven model and the mechanism model were determined by the measurement data, and the high-precision stress mapping results were obtained by combining the data-driven model data and mechanism model data. A monitoring platform was built for the unit hydraulic support column, and the unit hydraulic support column was used as the test object to carry out pressure tests of 600 kN, 800 kN, 1000 kN and 1200 kN. The test data of the four groups showed that the error between the stress mapping results and the measured value of the strain gauges was 3.086%, 1.783%, 1.182% and 1.548%, respectively. The mapping period is 0.32 s, which proves that the method can provide real-time and high-precision feedback on the stress state of the hydraulic column, realize real-time monitoring of the stress state of the hydraulic column, solve the problem that stress cannot be measured by attaching strain gauges in the complex underground environment, predict the fault and safety problems of the hydraulic column due to overload, and provide data reserve for the adaptive regulation of the hydraulic support.